Enhanced RRT* with APF and Halton Sequence for Robot Path Planning - Hameed, Mohammed T.; Raheem, Firas A.; Nasser, Ahmed R. (Journal of Robotics and Control (JRC), 2025)
This paper presents a new path planning method (APF-IRRT*-HS), which relies on the optimization process of the conventional RRT* algorithm and combined with the APF method where the sampling process of the RRT* algorithm is improved using the Halton sequence, which is known to be deterministic and repeatable and provides more efficient coverage than other low discrepancy sequences with the modified goal-based method which provides a probabilistic approach to decide whether to sample from a point directly at the target or to choose a random point from the Halton sequence based on the current distance. We implemented the proposed method in two cases of mass point and two-link robots. The proposed method compares path length with the conventional RRT* algorithm and APF-RRT*, as well as time efficiency and number of iterations. The technique proves effective in various dynamic environments. Specifically, the APF-IRRT*-HS algorithm achieved an improvement of approximately 21.88% and 7.5% in path length, 79.75% and 49.2% in computation time, and 57.39% and 40% in the number of iterations compared with the RRT* and RRT*-APF algorithms, respectively. We can use this method in everyday applications such as robotic arms, drones, self-driving cars, etc. More advanced methods, such as multi-link robots and real-time constraints, can be used in the future.